1994
DOI: 10.1143/jjap.33.991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dry Development Techniques using O2 and SO2/O2 Low-Pressure Plasmas

Abstract: A parametric study of the pattern transfer step in a trilevel resist system using oxygen-based plasmas has been performed using a distributed electron cyclotron resonance reactor with independent rf biasing. In pure oxygen plasmas, critical dimension loss is always present. The mechanisms most likely to be responsible for these defects during the pattern transfer process are presented and discussed. A novel plasma etching process based on sidewall passivation by sulfur is proposed using SO2/O2 mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…7,[11][12][13][14][15][16] In situ mass spectroscopy indicated similar etch products to those obtained while etching in a pure O 2 plasma such as H 2 O, CO and CO 2 . 7,[11][12][13][14][15][16] In situ mass spectroscopy indicated similar etch products to those obtained while etching in a pure O 2 plasma such as H 2 O, CO and CO 2 .…”
Section: Literature Surveymentioning
confidence: 83%
See 1 more Smart Citation
“…7,[11][12][13][14][15][16] In situ mass spectroscopy indicated similar etch products to those obtained while etching in a pure O 2 plasma such as H 2 O, CO and CO 2 . 7,[11][12][13][14][15][16] In situ mass spectroscopy indicated similar etch products to those obtained while etching in a pure O 2 plasma such as H 2 O, CO and CO 2 .…”
Section: Literature Surveymentioning
confidence: 83%
“…Using infrared ͑IR͒ and x-ray photoelectron spectroscopy ͑XPS͒, Chou et al observed a 1 nm structurally strained oxide layer on top of polysiloxane films exposed to an O 2 plasma that reduced the etching rate of the underlying film. 7 With pure O 2 plasmas, anisotropic profiles can be attained at ϳϪ100°C. 5 Plasma etching using an O 2 -only chemistry provides the high selectivities between the Si-containing and non-Sicontaining layers required for pattern transfer, but it is accompanied with considerable lateral etching and poor CD control.…”
Section: Literature Surveymentioning
confidence: 99%
“…Finally, low-temperature etching and associated wafer clamping can stress other film layers in integrated circuit fabrication. Based on recent reports, 7,8,14,15 we are currently investigating the effects of additives to the O 2 feed gas in the helicon in order to form anisotropic profiles at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…3,7-9 While using an O 2 -only etch chemistry gives high selectivities between the image layer and underlayer, there is considerable lateral etch and consequently poor critical dimension ͑CD͒ control which is believed to be caused by the spontaneous lateral etch by atomic oxygen. 13,14 Several gas additives to O 2 were studied in order to overcome these problems. N 2 -O 2 plasmas 5,15 and CO 2 -O 2 plasmas 5 resulted in improved linewidth control compared to O 2 -only plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…7͒ improved profile quality but did not decrease lateral etching. SO 2 /O 2 mixtures were shown to provide good profiles due to formation of a sidewall passivation layer 4,5,14,16,17 along with good selectivity. However, there are potential manufacturing issues with SO 2 as the sulfur-containing passivation layers form sulfur-based acids upon exposure to moisture.…”
Section: Introductionmentioning
confidence: 99%